2011
DOI: 10.4338/aci-2010-11-ra-0072
|View full text |Cite
|
Sign up to set email alerts
|

A trial of inpatient indication based prescribing during computerized order entry with medications commonly used off-label

Abstract: SummaryBackground: Requiring indications for inpatient medication orders may improve the quality of prescribing and allow for easier placement of diagnoses on the problem list. Indications for inpatient medication orders are also required by some regulators. Objective: This study assessed a clinical decision support (CDS) system designed to obtain indications and document problems during inpatient computerized physician order entry (CPOE) of medications frequently used off-label. Methods: A convenience sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…A previous study on indication-based prescribing systems has shown that an indication prompts may be able to improve problem list documentation [ 24 ], and by doing so, perhaps an indication-based prescribing system could assist prescribers to prescribe more appropriately in these situations. Another study on indication-based prescribing for off-label medications was encouraging in showing that decision support software could be deployed to help recommend on-label alternatives or off-label alternatives with a higher degree of evidence when the indication is entered by clinicians [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on indication-based prescribing systems has shown that an indication prompts may be able to improve problem list documentation [ 24 ], and by doing so, perhaps an indication-based prescribing system could assist prescribers to prescribe more appropriately in these situations. Another study on indication-based prescribing for off-label medications was encouraging in showing that decision support software could be deployed to help recommend on-label alternatives or off-label alternatives with a higher degree of evidence when the indication is entered by clinicians [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… • It has to be possible to link problems and interventions. Moreover when updating the original input of the problem list it should be possible to change the hierarchy of the problem list when the diagnosis becomes more precise [ 8 , 10 , 12 , 13 , 27 , 35 , 36 ] • A search function has to be implemented to prevent redundant entries [ 18 , 35 ] • The encoded list should be able to handle synonyms and free text entries or misspelled entries and should have an auto-suggestion feature [ 2 , 6 , 12 , 31 , 32 ] • Filter and custom views should be possible [ 8 , 12 , 18 , 24 ] • Clinical decision support should check the problem list and assist the clinician in filling out the problem list [ 15 , 21 , 25 , 26 , 33 – 35 , 37 ] • It has to be possible to specify coded entries further by providing free text at entry [ 12 ] • The problem list should work as a table of contents of the medical record [ 13 , 18 ] Interoperability Interoperability is the possibility to transfer data between systems without losing its information and context. • The problem list should be filled from all available clinical information systems to provide a complete view on the patient and not loose data entered in another system [ 2 , 18 , 28 , 37 ] • Problem list should have a dictionary/taxonomy behind them so codes from code systems, like ICD 9 ICD 10 and SNOMED, can be extracted, enlarging the interoperability [ 6 , 11 , 18 , 22 ] Multi-disciplinary The definition used in this article for multi-disciplinary is the combination of different clinicians and health professionals.…”
Section: Resultsmentioning
confidence: 99%
“… • In an EHR, providing overview of the patient data is of vital importance [ 8 , 27 ] • It should be possible to link problems and interventions, as problems are not always treated one at the time, to prevent fragmentation of the patients data [ 8 , 10 , 12 , 13 ] • The problem list should represent the patient data in a coherent and logical order, so it provides a cornerstone of the EHR, preventing errors due to missing information [ 11 , 15 , 18 , 21 , 25 , 36 ] • If well maintained and structured, a problem list can assist a multi-disciplinary approach [ 10 , 13 , 16 , 36 ] • Policy should help with constructing the overview of patient data, providing guidelines for adding or leaving problems of the list reducing confusion and preventing missing information [ 14 ] Quality of care The definition of quality of care is used in the broadest sense of the term, all which can influence the care of the patient. • If all patient information is related to problems and the problem list is often updated it allows for an evaluation of the efficacy of the treatment [ 7 , 13 , 15 , 22 , 33 ] • Communication and coordination between health professionals is supported by the problem list [ 7 , 10 , 15 , 18 , 21 , 22 ] • Clear policy on what to put on the problem list and for the users clear structure is essential [ 9 , 10 , 14 , 18 , 19 , 27 , 29 ] • The problem list is a valuable tool to get overview of the data of (unfamiliar) patients [ 7 , 8 , 11 , 12 , 14 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the Centers for Medicare & Medicaid Services requires nursing home patients to have an indication for all medications [3]. One intervention study prompted inpatient providers to document the indication for three specific medications if an appropriate one was not found on the problem list [20]. This study found including an associated indication at the time of prescribing increased, albeit these were often for off-label or non-evidence based use.…”
Section: Discussionmentioning
confidence: 99%